Insight into Magnetorheological Shock Absorbers - Gołdasz, Janusz; Sapiński, Bogdan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book deals with magnetorheological fluid theory, modeling and applications of automotive magnetorheological dampers. On the theoretical side a review of MR fluid compositions and key factors affecting the characteristics of these fluids is followed by a description of existing applications in the area of vibration isolation and flow-mode shock absorbers in particular. As a majority of existing magnetorheological devices operates in a so-called flow mode a critical review is carried out in that regard. Specifically, the authors highlight common configurations of flow-mode magnetorheological shock absorbers, or so-called MR dampers that have been considered by the automotive industry for controlled chassis applications. The authors focus on single-tube dampers utilizing a piston assembly with one coil or multiple coils and at least one annular flow channel in the piston.
Introduction -- MR Fluids -- Configurations of MR Dampers -- Modelling of Control Valves -- Damper Modelling -- CFD Study of the Flow of MR Fluids -- Power Drivers -- Experimental Verification of an MR Monotube Damper Model -- Energy Harvesting MR Dampers -- Concluding Remarks.
Keywords: Fluid mechanics; Machinery; Automotive engineering; Engineering Fluid Dynamics; Machinery and Machine Elements; Automotive Engineering